Comparison of Bolton's Ratios before and after Treatment in an Iranian Population - Asghar Ebadifar; Rojin Taliee (Tabriz University of Medical Sciences, 2013)
Background and aims. The correct relationship of the total mesiodistal width of the mandibular teeth to that of the maxillary teeth (Bolton's ratios) is among the main factors considered in obtaining an optimal occlusion. The present study was conducted to determining the Bolton's ratios before and after treatment in skeletal class I patients. Materials and methods. In this descriptive analytical study, 200 study casts of 100 patients (including 73 females and 27 males) were selected from 1,700 patient files with fixed, non-extraction orthodontic treatment protocol. The greatest mesiodistal width of teeth was measured using a digital caliper. The total Bolton index (TBI) and anterior Bolton index (ABI) were calculated for subjects and the obtained results were compared with the values reported by Bolton using one-sample ttest. The alterations in these indexes before and after treatment were compared with paired t-test. Results. Post-treatment ABI and TBI in patients were 77.35% ± 4.12% and 91.2% ± 1.66%, respectively. No significant difference was detected in ABI and TBI of patients after treatment when compared with the results of Bolton's study (P > 0.05). However, a significant correlation was observed in values of ABI (P < 0.001) and TBI (P < 0.01) before and after treatment. Conclusion. These findings suggest that patients with mild hypodontia have narrower teeth than normal subjects especially in posterior segments, which may have clinical implications during the orthodontic treatment process.